What is mental illness? - McNally, Richard J. (Belknap Press of Harvard University Press, 2011)
Discusses the classification process for mental illness, examining the difficulty that practitioners have of separating normal reactions to everyday stresses from true mental disorders, which involve recurring patterns of symptoms and behaviors.